Domination and Composition Structure Change at Hemic Peat Natural Regeneration Following Burning; A Case Study in Pelalawan, Riau Province - BAMBANG HERO SAHARJO; ATI DWI NURHAYATI (Biodiversitas Journal of Biological Diversity, 2006)
Biomass burning is the burning of the worldâ€™s living and dead vegetation, including grasslands, forests and agricultural lands following the harvest for land clearing and land-use change. One of the important information needed following this biomass burning is how long the burnt forest or land can be recovered, and how worst the changing occurred. Repeated burning occurred at the same place trend to clean the vegetation which leads to have the land with lower number and quality of species left. The research objective is to understand the vegetation changing following peat fires in the sapric peat type at the land preparation using belong to the local community located in the Pelalawan district, Riau province, Indonesia during the dry season in the year 2001. Before burning, logging, slashing, drying and burning the site was dominated by Uncaria glabrata at seedling stage, Ficus sundaica at sapling stage, Ficus sundaica at pole stage and Stenochlaena palustris at understorey. After logging, slashing and followed by 4 weeks drying then continued by burning with high flame temperature range from 900-1100oC, it had been found that 3-months following burning the site was dominated by Uncaria glabrata at seedling stage and Nephrolepis flaccigera at understorey while 6-months following burning the site was dominated by Parastemon uruphyllus at seedling stage and Erechites valeriantifolia at understorey stage. Â© 2006 Jurusan Biologi FMIPA UNS Surakarta Key words: peat fires, peat type, flame, natural regeneration, human.